Biofortified potato: Strategy and preparedness - Dalamu, Dalamu; Luthra, S K; Tiwari, J K; Sharma, Ashwani K (Indian Horticulture, 2020)
Nutrient deficiencies due to unbalanced dietary habits or unavailability of balanced food especially to poor people or by compulsion is an important health issue both in developed and developing countries. Different approaches of nutrient supplementation have their pros and cons. One such approach is biofortification. It is based on the principle of genetic manipulation of crop with enhanced nutrient content by plant breeding or biotechnological interventions and/or physical application of mineral micronutrient fertilizers to crop canopy or soil. The feasibility, efficacy and cost effectiveness of crop biofortification as a means of alleviating nutrient deficiency is scientifically proven. Here, at ICAR-CPRI, Shimla potato biofortification is targeted in breeding program that mainly focuses on enhancement of antioxidants (anthocyanins and carotenoids), iron and zinc contents in new biofortified potato varieties. Biofortification is a practical, sustainable, cost-effective approach to fulfill the nutritional requirements of weaker section of the society across the globe. Malnutrition, particularly hidden hunger, is a global phenomenon. In contrast to fortification, dietary diversification and nutrient supplementation, biofortification is a one-time investment required for development of biofortified varieties where the recurrent cost is similar to any existing crop variety. There is a need to know the effect and method of cooking, and storage as well as processing on nutrient content of biofortified varieties to optimize biofortification strategies. Moreover, awareness creation among masses, building of consumer demand and supply of adequate seed of biofortified varieties is required.